Effect of a moderately carbohydrate-restricted diet on liver enzymes, steatosis and fibrosis in normal-weight individuals with non-alcoholic fatty liver disease: study protocol for a parallel randomised controlled clinical trial - Ahmad Esmaillzadeh; Amir Ali Sohrabpour; Seyed Moayed Alavian; Fatemeh Dashti; Sara Ebrahimi Mousavi; Seyed-Ali Keshavarz (BMJ Open)
Introduction Non-alcoholic fatty liver disease (NAFLD) is a hepatic condition that is considerably prevalent across the world. Dietary intakes, in which macronutrient composition is precisely planned, might be able to reduce inflammation, steatosis and fibrosis among patients with NAFLD. A moderately carbohydrate restricted diet with weight loss has been demonstrated to improve liver fat content among overweight or obese patients. However, there is no information about the appropriateness of such a restriction, without weight loss, in normal-weight patients. This randomised clinical trial will be aimed at assessing the effect of moderate carbohydrate restriction on liver enzymes, liver steatosis and fibrosis in normal-weight patients with NAFLD.Methods and analysis This randomised controlled clinical trial will be conducted to evaluate the impact of a moderately carbohydrate restricted diet on liver enzymes, steatosis and fibrosis in 52 eligible normal-weight individuals with NAFLD. Transient elastography and controlled attenuation parameter with FibroScan will be applied to diagnose NAFLD. After individual matching based on body mass index, age and sex, patients will be randomly assigned to receive a moderately carbohydrate restricted diet or an isocaloric diet without carbohydrate restriction for 12 weeks. The primary and secondary outcomes in this study will be liver function indices, including liver steatosis and fibrosis, metabolic parameters and anthropometric measures. All these variables will be assessed at study baseline and postintervention.Ethics and dissemination The present clinical trial study was accepted by the ethics committee of TUMS (Tehran University of Medical Sciences) (code: IR.TUMS.MEDICINE.REC.1400.116).Trial registration number IRCT20210119050086N1.